Pengelolaan Lahan Kosong Melalui Penanaman Sayuran Hijau Teknik Hidroponik Sebagai Upaya Peningkatan Perekonomian Masyarakat Tahun 2019 - Arifin, Zainal; Makhmudah, Siti; Fauzi , Ahmad Masykurul; Rohmah, Ita Nur; Sari , Windi Erika; Huda, Chairul (Bisma : Bimbingan Swadaya Masyarakat, 2019)
This article discusses the management of vacant land through the cultivation of green vegetables using hydroponic techniques as an effort to improve the economic conditions of the community in 2019. Hydroponic agriculture is a method of growing plants without soil, where the plant roots are submerged in a nutrient-rich solution. The article emphasizes the advantages of hydroponic agriculture, such as higher yields and the ability to grow plants in areas with poor soil quality. Additionally, the cultivation of green vegetables has a high demand in the market, making it a profitable venture for small-scale farmers. The article highlights the importance of community involvement in the project, including training and education on hydroponic techniques and market analysis. Overall, the implementation of hydroponic agriculture in vacant lands has the potential to increase the income of small-scale farmers and contribute to the overall economic development of the community.